2013
DOI: 10.1186/1748-717x-8-72
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment planning target volumen (PTV) size on radiation induced diarrhoea following selenium supplementation in gynecologic radiation oncology - a subgroup analysis of a multicenter, phase III trial

Abstract: BackgroundIn a previous analysis (Int J Radiat Oncol Biol Phys 70:828-835,2010), we assessed whether an adjuvant supplementation with selenium (Se) improves Se status and reduces the radiation-induced side-effects of patients treated by adjuvant radiotherapy (RT) for cervical and uterine cancer. Now, a potential relation between the planning target volume (PTV) of the RT and the Se effect concerning radiation induced diarrhoea was evaluated in detail.MethodsWhole blood Se concentrations had been measured in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that 14 to 68% of patients with abdomen or pelvic tumors are treated with curative or palliative radiotherapy 25,31 . During the treatment, the incidence of anaemia, leukopenia, cystitis, diarrhoea and neuropathy rises to 84%, which is significantly more than after completion of the treatment 29,[32][33][34][35] . Grade 3 and 4 toxicity occurs in 4 to 40% of patients and correlates with the target volume size, fractionation regimen, received dose and radiation techniques 25,35,36 .…”
Section: Acute Radiation Toxicity -General Aspectsmentioning
confidence: 99%
“…Previous studies have shown that 14 to 68% of patients with abdomen or pelvic tumors are treated with curative or palliative radiotherapy 25,31 . During the treatment, the incidence of anaemia, leukopenia, cystitis, diarrhoea and neuropathy rises to 84%, which is significantly more than after completion of the treatment 29,[32][33][34][35] . Grade 3 and 4 toxicity occurs in 4 to 40% of patients and correlates with the target volume size, fractionation regimen, received dose and radiation techniques 25,35,36 .…”
Section: Acute Radiation Toxicity -General Aspectsmentioning
confidence: 99%
“…None of the selected trials reported survival rates or clinical response data, but a follow-up study assessed survival 6 years after 1 trial. 101,102 The study reported that there was no significant difference in 6-year survival between groups. 102 Buntzel et al 103 and Muecke et al 101 performed RCTs for patients undergoing radiotherapy for HNC, and cervical and endometrial cancer.…”
Section: Mineralsmentioning
confidence: 99%
“…101,102 The study reported that there was no significant difference in 6-year survival between groups. 102 Buntzel et al 103 and Muecke et al 101 performed RCTs for patients undergoing radiotherapy for HNC, and cervical and endometrial cancer. They concluded that selenium supplements reduced the number of episodes and the severity of radiotoxicities, such as dysphagia and diarrhea.…”
Section: Mineralsmentioning
confidence: 99%
See 2 more Smart Citations